Pengaruh Fraud Pentagon Theory Dalam Mendeteksi Kecurangan Laporan Keuangan (Studi Pada Perusahaan Bumn Yang Terdaftar Di Bei Periode 2019-2021) - Zefanya Nadya Putri; Sudarma, Made (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to determine the effect of the pentagon fraud theory in detecting fraudulent financial statements in State Owned Enterprises (BUMN) listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. By using purposive sampling for sampling methods, obtained 21 companies for three periods or as many as 63 samples. The analysis is performed using multiple linear regression analysis methods. The study's result indicates a significant influence of the nature of the industry and personal financial situation on fraudulent financial statements.